Kenya Economic Update, December 2012 : Kenya at Work, Energizing the Economy and Creating Jobs - World Bank (World Bank, Nairobi, 2017)
Kenya withstood another difficult year in 2012 as policy tightening and weaker global demand slowed economic activity. With decisive fiscal and monetary policies, the government managed to restore confidence in Kenya's medium term prospects. Kenya's growth rate is still below its potential and its peers, external imbalances remain which threaten its future growth, and the pace of economic growth is not generating enough modern sector wage jobs. With the passage of the new constitution in 2010 and its implementation, stronger institutions are emerging, putting Kenya on a sound footing ready to take off. In the very short term, what remains to be done is for Kenya to deliver a credible and peaceful election in March 2013, and thereafter a smooth transfer of power. In the medium term, Kenya will need to start building a stronger foundation for growth, and undertake structural reforms to correct the external imbalances. To generate more jobs for the burgeoning educated youth population, Kenya will also need to reduce the transaction cost for firms, by reducing job-smothering corruption and the cost of doing business (particularly in transport and energy).